Gestão sustentável dos resíduos sólidas: práticas na Universidade Federal da Paraíba quanto à destinação adequada dos cartuchos e toners. - Ventura, Hélia de Fátima Ramalho (2018)
The rapid increase in the industrial production of electrical and electronic equipment, such as printers, and consequently of cartridges and toners, can cause environmental consequences and human health if they are used without adequate management, especially in the final disposal process of the waste. The insertion of principles and practices of environmental sustainability can be a strategic means of planning institutional management, providing a new culture that encourages managers to add socio-environmental criteria. The present research had as general objective to investigate the environmental management practices regarding the destination of cartridges and toners of the Federal University of Paraíba (UFPB) and was characterized by being qualitative, field, cross-sectional and sample for convenience . Public servants from 10 sectors of the rectory and one sector of the vice rector participated in the survey. The instruments used were semi-structured questionnaires and interviews, besides the observation in loco, with photographic record. The quantitative data were tabulated in the Microsoft Excel 2010 software and analyzed by means of descriptive statistics from the construction of tables, tables and graphs. The qualitatively collected data were analyzed based on descriptions of interview information and photographic records. Through the collected data, it is noteworthy that in the UFPB, as well as in the other federal autarchies, the implantation of policies related to solid waste is recent. Thus, the present research presents a first diagnosis about the environmental policy of the UFPB, noting that the institution is aligned with the National Solid Waste Policy (PNRS) of 2010, highlighting the creation of the Environmental Management Commission (CGA) in 2013 , which performs some environmental actions, but has some challenges in the execution of these, since it is under construction in line with the national scenario. In this sense, the hypothesis of the present research is confirmed, since it was verified that the practice identified in the sectors interviewed is not effective against the demands of the environmental management regarding the destination of cartridges and toners of the UFPB. The fragility of operationalization and the recognition of the environmental actions undertaken, in light of a lack of concern or lack of interest in environmental concern, shared responsibility and environmental sustainability principles regarding the problem of adequate discards of solid waste (cartridges and toners) and its management, ignorance and exposure to the degree of danger that holds these materials makes important studies like this. Assuming that adequate operational and behavioral procedures for human activities in relation to the disposal of solid waste can reduce the environmental damages caused by them, it is appropriate to make some suggestions to improve the management of the socio-environmental practices of the institution, increased preparation of an educational manual on proper disposal of cartridges and toners and the restructuring of new policies for the management of cartridges and toners after consumption, regardless of their brands, etc. It is hoped that this work will enable the UFPB to expand and effectively practice environmental management in compliance with the principles of sustainability.